Experiential Marketing and Consumer Satisfaction: Study Meta Analysis - Mohammad Arief; Mochammad Isa Anshori; Ainul Yakin Anwari (International Journal of Social Service and Research, 2022)
This study examines the relationship between experiential marketing and consumer satisfaction. The meta-analysis technique uses with a sample of 36 articles published from 2010 to 2018. The artifact corrected is a sample error. This research aimed to integrating previous research. With the 95% confidence intervals, this study indicated that there is a significant influence between experiential marketing and consumer satisfaction (r = 0.507). Furthermore, this study also found that there's a significantly influences from sense, fell, think and relate to consumer satisfaction. Moreover, the influence between experiential marketing and consumer satisfaction is strong. The results of the meta-analysis also show the average value of population correlation from sense, feel, think, act and relate to customer satisfaction.